2008
DOI: 10.1086/526438
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial and Meta-analysis of Oral Decontamination with 2% Chlorhexidine Solution for the Prevention of Ventilator-Associated Pneumonia

Abstract: Oral decontamination with 2% chlorhexidine solution is an effective and safe method for preventing VAP in patients who receive mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
165
0
16

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(201 citation statements)
references
References 18 publications
1
165
0
16
Order By: Relevance
“…Chlorhexidine at varying concentrations, however, has been evaluated in more than 11 trials. Impacts on VAP rates have been variable: three reported decreases [64][65][66] while the other eight did not [67][68][69][70][71][72][73][74]. One trial reported a decrease in antibiotic usage for patients treated with chlorhexidine [67].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%
“…Chlorhexidine at varying concentrations, however, has been evaluated in more than 11 trials. Impacts on VAP rates have been variable: three reported decreases [64][65][66] while the other eight did not [67][68][69][70][71][72][73][74]. One trial reported a decrease in antibiotic usage for patients treated with chlorhexidine [67].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%
“…A recent meta-analysis concluded that use of oral chlorhexidine might be effective in preventing lower respiratory tract infections in patients receiving mechanical ventilation for up to 48 hours, although its impact in preventing late-onset VAP requires further research. 8 Remarkably, none of those meta-analyses, or the study by Tantipong et al 1 demonstrated any impact on mortality.…”
Section: E T T E R S T O T H E E D I T O R Prevention Of Ventilatormentioning
confidence: 96%
“…To the Editor-We read with interest the article by Tantipong et al 1 on the use of oral decontamination with 2% chlorhexidine solution for the prevention of ventilator-associated pneumonia (VAP). We believe that their study has some important limitations and that the authors' conclusion that oral chlorhexidine is an effective and safe method for VAP prevention is not supported by the results.…”
Section: E T T E R S T O T H E E D I T O R Prevention Of Ventilatormentioning
confidence: 99%
See 1 more Smart Citation
“…(42) The literature reports a wide variety of treatment regimens using chlorhexidine, including variations in concentration (0.2%, 0.12% and 2%), site of application, form of presentation (oral rinse or gel) and application techniques. (32,42,43) Studies involving cardiac surgery patients at a low risk for VAP reported that chlorhexidine at 0.12% was effective; however, higher concentrations might be required for more heterogeneous populations in a hospital environment, since the use of chlorhexidine at 2% in these populations seemed to produce better results. (32) The association between oral decontamination using topical antiseptic agents and the time spent in the ICU, mortality or duration of MV is not always evident; however, a reduction in the incidence of pneumonia has been observed in all studies.…”
Section: Prevention Of Nosocomial Pneumonia: Importance Of Oral Hygiementioning
confidence: 99%